Exploring Couple Dynamics from a Gender Perspective among Career Women in Healthcare Settings - Handayani, Wuri; Mutiara Dewi, Ita; Disyacitta, Fikri; Salafian, Jen (Fisip UIN Sunan Gunung Djati Bandung, 2025)
This study examines gender relations and role dynamics among women working in health services (Puskesmas). The research conducted in depth interviews to uncover the paradox in the workplace with eight months of PAR involving 15 healthcare workers in Yogyakarta. Although the majority of health workers are women, organisational structures and leadership practices continue to adhere to masculine values, such as assertiveness in decision making. This creates a workplace where women are underrepresented in leadership roles. In the domestic sphere, the main findings of this service demonstrate that women working in professional fields face a double burden, characterised by the phenomenon of two shifts, where they are solely responsible for both their household and professional responsibilities. This physical and mental burden places women in the role of home coordinator and family emotional bearer. In couple relationships, a collaborative or team model is used, but patriarchy remains, albeit modified. Couples maintain symbolic boundaries of masculinity and patriarchy in the form of cultural residue. Despite this, the interviewees demonstrate a high level of critical awareness, viewing nature as a social construct, rejecting rigid gender dichotomies, and adopting a flexible and functional understanding of gender.